Management across boundaries: A municipal dilemma. (15th March 2018) - Thomasson, Anna
Abstract: Public sector mergers have the potential of being viable alternative to other public sector reforms in the striving toward making public service provision more equipped to confront some of the challenges faced today. Mergers however often fail to deliver promised results. Previous research point to the importance of post‐merger integrating processes for realizing the synergies expected from mergers. However, so far these studies have focused on what occurs inside organizations and less on the interplay between different levels. By adopting a governance and top management perspective, this study increases our understanding of the importance of political decisions on the outcome of a merger in the public sector context. Further, this study increases our understanding of how organizational boundaries on different levels of merging organizations influence post‐merger integrating processes and the role of different actors as boundary spanners. The results of this study are based on five case studies of public sector mergers at the local level in Sweden.